Meteor solutions : measuring the value of social media marketing - Jeffery, Mark, 1965- (SAGE Knowledge. Cases., 2017)
In March 2009, Steve Fowler, vice president of strategy and client service at full-service advertising agency Ayzenberg, had just completed what he considered to be one of the most innovative campaigns he had ever handled. Capcom, a leader in the video gaming industry, had just launched Resident Evil 5 (RE5), the latest release of one of the industry's most valuable game franchises. RE5, a powerful asset with a passionate fan base, had warranted the use of an online viral, or word-of-mouth (WOM), campaign for its worldwide game launch. Although the creative work and appropriate media for the RE5 launch had been meticulously planned, Fowler was also interested in measuring the effectiveness of the campaign to better serve his client. In the past, measuring WOM was practically impossible. However, a software company named Meteor Solutions had found a way to do exactly that. Fowler and his team had worked with Meteor to execute several campaigns for other clients, but he had never applied Meteor tools on such a large scale. Fowler knew Capcom would want to hear specific WOM figures. What was the return on investment for the RE5 campaign and the implications for future campaigns? Had the Meteor tools provided comprehensive and actionable information, or was more work needed before these solutions could be widely used in advertising?